Use of recombinant microRNAs as antimetabolites to inhibit human non-small cell lung cancer - Yixin Chen; Mei-Juan Tu; Fangwei Han; Zhenzhen Liu; Neelu Batra; Primo N. Lara; Hong-Wu Chen; Huichang Bi; Ai-Ming Yu (Elsevier, 2023)
During the development of therapeutic microRNAs (miRNAs or miRs), it is essential to define their pharmacological actions. Rather, miRNA research and therapy mainly use miRNA mimics synthesized in vitro. After experimental screening of unique recombinant miRNAs produced in vivo, three lead antiproliferative miRNAs against human NSCLC cells, miR-22-3p, miR-9-5p, and miR-218-5p, were revealed to target folate metabolism by bioinformatic analyses. Recombinant miR-22-3p, miR-9-5p, and miR-218-5p were shown to regulate key folate metabolic enzymes to inhibit folate metabolism and subsequently alter amino acid metabolome in NSCLC A549 and H1975 cells. Isotope tracing studies further confirmed the disruption of one-carbon transfer from serine to folate metabolites by all three miRNAs, inhibition of glucose uptake by miR-22-3p, and reduction of serine biosynthesis from glucose by miR-9-5p and -218-5p in NSCLC cells. With greater activities to interrupt NSCLC cell respiration, glycolysis, and colony formation than miR-9-5p and -218-5p, recombinant miR-22-3p was effective to reduce tumor growth in two NSCLC patient-derived xenograft mouse models without causing any toxicity. These results establish a common antifolate mechanism and differential actions on glucose uptake and metabolism for three lead anticancer miRNAs as well as antitumor efficacy for miR-22-3p nanomedicine, which shall provide insight into developing antimetabolite RNA therapies.